Evaluation of low code and no code platforms as a strategy to increase productivity in software development - Silva, Juciê Xavier; Avelino, Guilherme (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2024)
Since the beginning of the digital era, the software industry has faced a constant and growing demand for sophisticated technological solutions. This accelerated demand has intensified the search for improvements in development productivity and efficiency. Over the years, several strategies and innovations have been proposed, with emphasis on the low code and no code development platforms. This study analyzed these platforms, with a special focus on claims of substantial improvements in productivity. To this end, a two-stage methodology was adopted. The first stage consisted of a multivocal literature review, aiming to extract as much information as possible about the benefits and challenges of these platforms. In the second stage, the findings of the literature review were analyzed in practice through an empirical case study that involved the development of a prototype to promote selective waste collection, composed of three profiles (Collector, Producer and Recycler) and developed using the OutSystems and Bubble platforms. The objective was to correlate theory and practice and provide a comprehensive analysis. As a result of the study, it was possible to observe a series of advantages and challenges associated with the use of these platforms. The advantages include code abstraction, automation of repetitive tasks, component reuse, and simplification of collaboration between members of the development team. Challenges such as platform dependency, technical expertise requirements, limited functionality, and data security concerns were also identified. As contributions, this research offers an empirical evaluation of the Outsystems low code and Bubble no code platforms, presenting their impact on software development productivity.